(untitled) (Italiano LinguaDue, 2020)
The DELCYME project offers a self-learning platform to improve knowledge and culture for young professionals who will carry out an internship in a country with one of the following target languages: German, French, Spanish, Italian or Polish. The course is personalized for each learner and the topics covered are linked to both daily and working life. The authors of the project aim to define activities adapted to each level, select or create course materials, propose a progression and create tasks, from simple to more complex levels. Lesson design and the final task involve several participants. In this article, we will explore how the creation process can be described and defined by the terms empathy and mediation. Empatia e mediazione: creare un corso online Il progetto DELCYME offre una piattaforma di autoapprendimento per migliorare la conoscenza e la cultura di giovani professionisti che svolgeranno un tirocinio in un paese con una delle seguenti lingue target: tedesco, francese, spagnolo, italiano o polacco. Il corso è personalizzato per ogni studente e gli argomenti trattati sono legati sia alla vita quotidiana che a quella lavorativa. Gli autori del progetto mirano a definire attività adatte ad ogni livello, selezionare o creare materiali per il corso, proporre una progressione e creare compiti, dai livelli più semplici a quelli più complessi. La progettazione della lezione e il compito finale coinvolgono diversi partecipanti. In questo articolo esploreremo come il processo di creazione può essere descritto e definito con i termini empatia e mediazione.